Landscape Design Principles For Visually Impaired Schools - Ayaat Ahmed Mohamed (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2023)
The building consists of a series of spaces that interact with each other, forming the school building which contains/ encloses the educational process, as well as a series of activities that control the design of the school spaces. The design of these spaces depends on the nature of its intended activity and the requirements of this activity. The elements, requirements and design of the educational building vary according to the educational need, as well as the type and nature of the disability.Since existing schools are not suitable for integrating disabled persons with their ordinary colleagues, the architectural and physical space of the schools must be tailored to fit the needs of this group, so that children with disabilities can continue to be educated alongside their ordinary colleagues in order to integrate them into society and reduce their overall dependence on others both within and outside their families.The subjects directly related to the design of open spaces in schools for the visually disabled have been studied, and the impact of these subjects on the child's behavior and on the improvement of his/her functions as a user has been determined. Furthermore, this research studied the design elements of the open spaces and external location and their relationship with the visually disabled child as a user, the extent to which they affect his/her development, upbringing, interaction awareness of the surrounding place, and the extent to which he/she meets his/her needs.